The impact of electronic payment systems on the velocity of money circulation - Taha Talib Mohammed Al- Tweel, Ali Hassan Zayer, (Opción, 2019)
The aim of the study is to investigate the impact of electronic payment systems on the velocity of money circulation via comparative qualitative research methods. As a result, the bank has strived to have one of the best electronic payment systems since 2006 to apply the system as an essential step to develop the Iraqi banking sector and increase its efficiency and effectiveness in achieving financial stability in the country through the money circulation electronically. In conclusion, the electronic payments system reduced the need to carry money and thus reduced the risk of theft, loss, and damage.